Targeting the Mutational Landscape of Bystander Cells: Drug-Promoted Blood Cancer From High-Prevalence Pre-neoplasias in Patients on BRAF Inhibitors - Simnica, Donjete; Ittrich, Harald; Bockemeyer, Carsten; Stein, Alexander; Binder, Mascha (Frontiers in Oncology, 2020)
Drug-promoted cancers are increasingly recognized as a serious clinical problem in patients receiving BRAF inhibitory treatment. Here we report on a patient with BRAF mutant hairy cell leukemia and monoclonal B-cell lymphocytosis (MBL), who responded durably to BRAF/MEK inhibitors (BRAFi/MEKi) but experienced transformation of a RAS mutant MBL to chronic lymphocytic leukemia (CLL) with accelerated nodal progression. Hypothesizing that BRAFi triggered excessive MEK-ERK signaling in the MBL/CLL clone via the CRAF/RAS complex as previously described for BRAFi-induced cancers, BRAFi was discontinued inducing a rapid remission of the CLL on MEKi alone. Liquid biopsy monitoring showed a continuous increase of the MBL/CLL clone from the start of BRAFi/MEKi treatment followed by a rapid decline upon BRAFi withdrawal. Next-generation sequencing of a cohort of patients with MBL and monoclonal gammopathy of unclear significance (MGUS) revealed that almost one third of these cases harbored RAS mutations. In view of the population frequency of lymphatic pre-malignant conditions and the prevalence of RAS mutations in such cases, vigilant surveillance remains critical in patients treated with BRAF inhibitors.